The expression pattern of matrix metalloproteinases (MMP-1, MMP-2, MMP-8, MMP-13) in relation of CTCF and YB-1 protein interactions on human cancer cell lines - Nur Aizura binti Mat Alewi (Kulliyyah of Allied Health Sciences International Islamic University Malaysia, 2015)
Collagenases, which are proteins from the matrix metalloproteinases family, have been implicated to play a crucial role in tumor invasion. Previous studies have also suggested that collagenases may have a significant influence in the expression of CTCF and YB-1 proteins, which have also been implicated in numerous cancer studies. However, the depth of its involvement in the fundamental molecular mechanisms of cancer remains to be poorly known. This study aims to determine the degree of MMP-1, MMP-8, MMP-13, YB-1 and CTCF protein expressions in breast, cervix and skin human cancer cell lines and to ascertain its probable involvement in cancer development. An ELISA assay was conducted in order to estimate the concentration of the proteins that could be found in the cells. The quantitative expressions of MMP-13 proteins in A375, MCF-7 and HeLa cells were evaluated through ELISA test. The results showed a marked expression of MMP-13 proteins in MCF-7 (12900 pg/mL), followed by HeLa (8109 pg/mL) and A375 (7515 pg/mL). This correlated to the Western blot assay where MCF-7 showed the strongest protein expression followed by HeLa and A375. The qualitative expressions of the proteins in cervix cancer (HeLa), breast cancer (MCF-7), skin melanoma (A375) and normal fibroblast (CCD1090Sk) cells were demonstrated through Western Blot analysis. The results showed that the strongest expression for MMP-1 was detected in HeLa cells at ~52 kDa, while MCF-7 and A375 cells produced very weak or almost non-detectable protein expressions. In contrast, MMP-8, MMP-13, CTCF and YB-1 proteins were highly expressed at varying degree of expressions in all cell lines. For MMP-8 analysis, multiple bands were detected at ~70 to 45 kDa, while MMP-13 only produced a single band at ~48 kDa. The results also showed the detection of CTCF protein bands ranging from ~180 to ~80 kDa and YB-1 protein expressions at ~55 kDa. In Co-Immunoprecipitation assay, results showed that most of the protein-protein interactions caused the expressions of most of the proteins to be highly up-regulated though some of the interactions also resulted in a decreased in protein expression. It was taken note that although the molecular mass of the proteins correlated to its respective Western blot assay results, their protein expressions were either highly expressed or were of less prominence. It was elucidated that the increase and decrease of the protein expression may have been caused by the interactions and binding of the proteins to its protein partners which then affect cellular regulation. Overall, although variations were found in the expression of the collagenase in various human cancer cell lines, the results depicted a prominent presence and the probable involvement of MMP-1, MMP-13, YB-1 and CTCF proteins in the development and metastasis of cancer. Thus, it is believed that obtaining a detailed understanding of collagenases and its interacting partners may be vital for future endeavours in respect to the possible design of therapeutic MMP strategies for prospective targeted human therapeutic treatments.